The Coming-Out Process in Family, Social, and Religious Contexts Among Young, Middle, and Older Italian LGBQ+ Adults - Rosati, Fausta; Pistella, Jessica; Nappa, Maria Rosaria; Baiocco, Roberto (Frontiers in Psychology, 2020)
The coming out (CO) process is fundamental for identity integration among LGBQ+ people, and its impact can vary greatly depending on personal and contextual factors. The historical, cultural, and social contexts in which LGBQ+ people develop their sexual identity can mediate the relationship between CO and health outcomes. The present study aimed at clarifying the CO process in three generations of Italian LGBQ+ people (young adults: aged 20–40 years; middle adults: aged 41–60 years; older adults: aged 61–80 years) by providing data on: (a) sexual orientation milestones, such as age of first awareness, age of first self-label, and age of first CO, as well as the rate of disclosure during different life stages; (b) the rate and average age of CO to significant others; and (c) CO within the religious context and its effect on participants’ minority stress experiences. A total of 266 Italian LGBQ+ people participated in the study, with ages ranging from 20–80 years (M = 41.15, SD = 16.13). Findings indicated that, on average, the older adult group became self-aware, self-labeled, and disclosed their sexual identity at a significantly older age than the other groups. Older adults were also more Catholic and had CO more frequently to their Catholic community, relative to young and middle adults. CO within the Catholic context was associated with distal and proximal minority stressors, such as discrimination, vigilance, and internalized sexual stigma. Catholic community reactions to participants’ CO were distinguished through thematic analysis in three main types: unconditional acceptance, invitation to change, and open rejection. The present research extended current knowledge on CO and minority stress experiences in different generations of LGBQ+ people. Several differences emerged between generational groups on sexual orientation milestones, highlighting the potential impact of historical and cultural contexts in determining sexual minorities’ experiences related to sexual identity. It is recommended that mental health professionals working with LGBQ+ clients implement targeted interventions based on their clients’ multiple salient aspects, including age and religious background. Clinicians should also be aware of the potentially detrimental effects of CO within an unsupportive context, rather than encouraging CO tout court.